6(-2a-4b) + 3(-7b-5a) = -(12(a+2b)+3(5a+7b)) = -3(4a+5a + 8b+7b)

= -3(9a+15b) = -9(3a+5b)

-4b(2a-6b) + 5(7ab-2b

3(1-7x) - 4(-4+10x) = 3 - 21x +16 - 40x = 19-61x

7a - (-2b - 3(4a - (6b-4a))) = 7a - (-2b - 3(4a - 6b + 4a))

= 7a - (-2b - 3(8a - 6b)) = 7a - (-2b - 24a + 18b) = 7a - (-24a + 16b)

= 7a + 24a - 16b = 31a-16b

Your instructor may require the first two to be multiplied out. (The 1st and 4th problems in your list are duplicates.)

= -3(9a+15b) = -9(3a+5b)

-4b(2a-6b) + 5(7ab-2b

^{2}) = b(-8a+24b + 35a-10b) = b(27a+14b)3(1-7x) - 4(-4+10x) = 3 - 21x +16 - 40x = 19-61x

7a - (-2b - 3(4a - (6b-4a))) = 7a - (-2b - 3(4a - 6b + 4a))

= 7a - (-2b - 3(8a - 6b)) = 7a - (-2b - 24a + 18b) = 7a - (-24a + 16b)

= 7a + 24a - 16b = 31a-16b

Your instructor may require the first two to be multiplied out. (The 1st and 4th problems in your list are duplicates.)